Immune selection for altered antigen processing leads to cytotoxic T lymphocyte escape in chronic HIV-1 infection. - Draenert, R; Le Gall, S; Pfafferott, K; Leslie, A; Chetty, P; Brander, C; Holmes, E; Chang, S; Feeney, M; Addo, M; Ruiz, L; Ramduth, D; et al. (2004)
Mutations within cytotoxic T lymphocyte (CTL) epitopes impair T cell recognition, but escape mutations arising in flanking regions that alter antigen processing have not been defined in natural human infections. In human histocompatibility leukocyte antigen (HLA)-B57+ HIV-infected persons, immune selection pressure leads to a mutation from alanine to proline at Gag residue 146 immediately preceding the NH2 terminus of a dominant HLA-B57-restricted epitope, ISPRTLNAW. Although N-extended wild-type or mutant peptides remained well-recognized, mutant virus-infected CD4 T cells failed to be recognized by the same CTL clones. The A146P mutation prevented NH2-terminal trimming of the optimal epitope by the endoplasmic reticulum aminopeptidase I. These results demonstrate that allele-associated sequence variation within the flanking region of CTL epitopes can alter antigen processing. Identifying such mutations is of major relevance in the construction of vaccine sequences.